Pelayanan Pembuatan Media Dan Alat Main Untuk Pengembangan Profil Pelajar Pancasila Anak Usia Dini Dalam Keluarga Hindu Di Kota Mataram - Rasmini, Ni Wayan; Karta, I Wayan (IAHN Gde Pudja Mataram, 2023)
This community service activity aims to increase the knowledge and skills of parents/caregivers in stimulating playing activities at home which can be a complement to education and learning that occurs in schools. Activities carried out by the community service team, with a target of 30 AUD parents/caregivers at home. The methods applied are direct learning methods, giving assignments, problem-based learning, cases, and collaborative projects. Methods of data collection using observation guidelines with a Likert scale (4, 3, 2, 1) and analysis of the work. The data obtained is in the form of interval data, and analyzed using descriptive statistics to determine the level of achievement of this PKM result. The conclusion obtained: the average achievement of knowledge and skills reaches a good category, there is one very good aspect of knowledge and skills, namely the preparation of outlines of plans for children's activities at home. Increasing parents' knowledge and skills in stimulating activities at home is expected to optimize children's growth and development achievements and the profile of Pancasila early childhood students.